Haemophagocytic lymphohistiocytosis in adults: a multicentre case series over 7 years. (5th November 2015) - Schram, Alison M.; Comstock, Paige; Campo, Meghan; Gorovets, Daniel; Mullally, Ann; Bodio, Kelly; Arnason, Jon; Berliner, Nancy
Summary: Haemophagocytic lymphohistiocytosis (HLH) is a syndrome of uncontrolled immune activation that has gained increasing attention over the past decade. Although classically known as a familial disorder of children caused by mutations that affect cytotoxic T‐cell function, an acquired form of HLH in adults is now widely recognized. This is often seen in the setting of malignancy, infection or rheumatological disorders. We performed a retrospective review across 3 tertiary care centres and identified 68 adults with HLH. The average age was 53 years (range 18–77 years) and 43 were male (63%). Underlying disorders included malignancy in 33 patients (49%), infection in 22 (33%), autoimmune disease in 19 (28%) and idiopathic HLH in 15 (22%). Patients were treated with disease‐specific therapy and immunomodulatory agents. After a median follow‐up of 32·2 months, 46 patients had died (69%). The median overall survival was 4 months (95% CI: 0·0–10·2 months). Patients with malignancy had a worse prognosis compared to those without (median survival 2·8 months versus 10·7 months, P = 0·007). HLH is a devastating disorder with a high mortality. Further research is needed to improve treatment and outcomes.